1983
DOI: 10.1159/000206684
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Granulopoiesis in Patients with Untreated Graves’ Disease

Abstract: Total and differential leucocyte countings, mobilization of the marrow granulocyte reserve with hydrocortisone and growth of blood colony-forming cells (CFU-C) in agar culture have been evaluated in 17 patients with Graves’ disease before therapy. Moreover, the myeloid differentiation of blood CFU-C in liquid culture has been studied in 4 patients. Neutropenia was found in only 1 patient (5.9%), while the marrow granulocyte reserve was reduced in 7 out of 15 patients (46.7%). Blood concentration of CFU-C and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
5

Year Published

1987
1987
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
(9 reference statements)
0
15
0
5
Order By: Relevance
“…17,18 Another study proposed abnormal granulopoiesis and decreased marrow granulocyte reserve as the possible mechanisms for neutropenia. 19 Higher leucocyte numbers and neutrophil counts in smokers as compared to nonsmokers are well described. 8,9 Smokers also have higher haemoglobin concentrations because of relative hypoxia and higher carboxyhaemoglobin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,18 Another study proposed abnormal granulopoiesis and decreased marrow granulocyte reserve as the possible mechanisms for neutropenia. 19 Higher leucocyte numbers and neutrophil counts in smokers as compared to nonsmokers are well described. 8,9 Smokers also have higher haemoglobin concentrations because of relative hypoxia and higher carboxyhaemoglobin.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown an association of neutropenia with the presence of antineutrophil antibodies . Another study proposed abnormal granulopoiesis and decreased marrow granulocyte reserve as the possible mechanisms for neutropenia …”
Section: Discussionmentioning
confidence: 99%
“…Bei bis zu 31% der Patienten mit Morbus Basedow und assoziierter Beteiligung der äußeren Augenmuskulatur (MorbusBasedow-assoziierte Ophthalmopathie, BAO) sind antinukleäre Antikörper nachweisbar.Bei einem Morbus Basedow ohne Augenmuskelbeteiligung fehlt gewöhn-lich der ANA-Nachweis [14]. Eine Zuordnung zu einem bestimmten Zielantigen innerhalb der antinukleären AK gelingtwie in unserem Fall -jedoch meist nicht.…”
Section: Diskussionunclassified
“…Hämatologische Veränderungen wie Anämie (34%), Leukozytopenie (5,8-20%),und Thrombozytopenie (3,3%) werden beschrieben [3,7,14]. Für die hä-matologischen Veränderungen werden sowohl immunologische als auch metabolische (erhöhte "turn-over"-Rate bei hyperthyreoter Stoffwechsellage) Mechanismen diskutiert [3,7,14].…”
Section: Diskussionunclassified
See 1 more Smart Citation